Phytodepuration of Nitrate Contaminated Water Using Four Different Tree Species - Luca Regni; Maria Luce Bartucca; Euro Pannacci; Francesco Tei; Daniele Del Buono; Primo Proietti (Plants, 2021)
Water pollution by excessive amounts of nitrate (NO3−) has become a global issue. Technologies to clean up nitrate-contaminated water bodies include phytoremediation. In this context, this research aimed to evaluate four tree species (Salix alba L., Populus alba L., Corylus avellana L. and Sambucus nigra L.) to remediate nitrate-contaminated waters (100 and 300 mg L−1). Some physiological parameters showed that S. alba L. and P. alba L. increased particularly photosynthetic activity, chlorophyll content, dry weight, and transpired water, following the treatments with the above NO3− concentrations. Furthermore, these species were more efficient than the others studied in the phytodepuration of water contaminated by the two NO3− levels. In particular, within 15 days of treatment, S. alba L. and P. alba L. removed nitrate quantities ranging from 39 to 78%. Differently, C. avellana L. and S. nigra L. did not show particular responses regarding the physiological traits studied. Nonetheless, these species removed up to 30% of nitrate from water. In conclusion, these data provide exciting indications on the chance of using S. alba L. and P. alba L. to populate buffer strips to avoid NO3− environmental dispersion in agricultural areas.